The Emperor’s New Clothes, Kecurangan Akademik di Pemerintahan: Perspektif Teori Kritis - Noor Azlin Tauchid, M.Krim (The Prosecutor Law Review, 2025)
This paper examines the pervasive issue of academic dishonesty in Indonesia, focusing on its structural and cultural underpinnings rather than treating it as a mere matter of individual misconduct. Drawing on Critical Theory—particularly the perspectives of Michel Foucault, Antonio Gramsci, and Theodor Adorno—it situates practices such as plagiarism, data fabrication, ghostwriting, and the acquisition of fraudulent credentials within broader systems of power, hegemony, and instrumental rationality. Drawing inspiration from folktales The Emperor’s New Clothes, this writing analysis reveals how institutional pressures, bureaucratic performance metrics, credential fetishism, and the normalization of unethical practices create a regime of truth that paradoxically produces and legitimizes academic dishonesty. By framing these practices as systemic byproducts of governance structures rather than isolated violations, the paper underscores the need for transformative cultural and structural reforms. Such reforms must address the ideological and institutional frameworks that sustain academic misconduct, reconfigure incentive systems, and restore education’s role as a domain for ethical knowledge production, critical inquiry, and human emancipation.